2014
DOI: 10.1590/1678-6654
|View full text |Cite
|
Sign up to set email alerts
|

A utilização de glicerina em dietas para bovinos altera a microbiota ruminal

Abstract: A utilização de glicerina em dietas para bovinos altera a microbiota ruminal [The use of glycerin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
5
2
Order By: Relevance
“…Crude glycerin addition to diets did not affect the concentration of protozoa. This result contrasts to that reported by Fávaro et al (2014), who showed a decrease in the LAP with inclusion of up to 20% crude glycerin in cattle diets. Here we found that LAB were also not affected, suggesting that both microorganism fractions associated with the liquid phase of rumen content was not affected by crude glycerin inclusion.…”
Section: Protozoal and Bacterial Fractionscontrasting
confidence: 99%
“…Crude glycerin addition to diets did not affect the concentration of protozoa. This result contrasts to that reported by Fávaro et al (2014), who showed a decrease in the LAP with inclusion of up to 20% crude glycerin in cattle diets. Here we found that LAB were also not affected, suggesting that both microorganism fractions associated with the liquid phase of rumen content was not affected by crude glycerin inclusion.…”
Section: Protozoal and Bacterial Fractionscontrasting
confidence: 99%
“…Moreover, considering that approximately 43% of glycerol is absorbed through the ruminal wall (Krehbiel 2008), it probably contributes to the reduction of subtract available to LAB. The lack of effect of crude glycerin on liquid-associated protozoa disagrees with the results presented by Fávaro et al (2014) who observed linear decrease of LAP, when feeding crossbred steers with 0, 50, 100, 150, or 200 g kg −1 crude glycerin. In current study, it expected a reduction in LAP yield due to the reduction of LAB, which is engulfed by protozoa as its main protein source.…”
Section: Treatments Acontrasting
confidence: 97%
“…Possibly this is because part of the glycerol has a rapid absorption in the rumen wall to be metabolized in the liver to glucose and another part is fermented to propionate, which will also be converted into glucose. Fávaro et al (2014) found that 43% of the glycerol that reaches the rumen disappears by absorption by the rumen wall and 44% by fermentation, the main product of fermentation being propionate, which is a precursor of volatile fatty acids and metabolic glucose in ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the lactose levels are within the required standards, however the fat levels are below the minimum value established by the legislation in all treatments. Studying the effect of glycerin on the ruminal microbiota of cattle Fávaro et al (2014) reported that the economic viability of using glycerin in animal feed depends on the price relationship between ingredients, especially corn and soybean oil or other energy source. Lage et al (2014) recommended that glycerin emerges as an option in the formulation of diets, being able to replace corn, when the price represents up to 70% of the price of corn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation